MENGGUGAT PUTUSAN MAHKAMAH KONSTITUSI TENTANG PENCALONAN MANTAN NARAPIDANA DALAM PEMILU - Jamaludin Ghafur (Penerbit Universitas Atma Jaya Yogyakarta, 2019)
The constitutional court through its decision No. 42 / PUU-XIII / 2015 states that all ex-convicts may run in elections as long as their political rights are not revoked by the court. They are only required to honestly and openly announce to the public about their convict status. according to the Court, the limitation and even revocation of the political rights of ex-convicts must not be carried out by lawmakers through legislation instruments but must be with a court decision as regulated in Article 35 paragraph (1) number 3 of the Criminal Code. This decision is not entirely correct for two reasons. First, Indonesia as a country that adheres to a continental European legal system (civil law system), the law has a higher position as a source of law (primary sources of law). Whereas the court's decision only as one of the secondary sources of law. Second, the conflict between the Election Law and the Criminal Code should be resolved according to the lex specialis derogat legi generalist principle. Thus, the prohibition for ex-convicts to run for the election as regulated in the Election Law should be interpreted as a specialist regulation so that it can override the provisions contained in the Criminal Code.